2021
DOI: 10.1002/bsd2.178
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the nexus between business activity and development aid in favor of the development agenda

Abstract: This article explores the connections between business activity and development aid that can help achieve the sustainable development goals placed by the United Nations (UN) in its development agenda. The article relies on an exhaustive review of the recent literature on development aid in the context of the European Community of West African States (ECOWAS). Connections exist between private firms' activity and both private and official aid, as firms can engage in business philanthropy, impact migrants' remit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 131 publications
(137 reference statements)
0
4
0
Order By: Relevance
“…), key information relative to the articles' approach (e.g., theoretical background and type of empirical study), aid characteristics and impact on firms' international growth was identified, analysed and manually coded by the research team following the scheme in Table 2. We followed López‐Duarte and Vidal‐Suárez (2021) to classify ODA flows according to different criteria (e.g., multilateral/bilateral, conditioned aid, ODA formulas, recipients' needs, donors' interests and tied aid). Recipient countries were classified according to their level of income (four categories by the OECD) and type of government (three categories of democratic development by the Economist Intelligence Unit).…”
Section: Methodology: Identification Selection and Analysis Of Articlesmentioning
confidence: 99%
“…), key information relative to the articles' approach (e.g., theoretical background and type of empirical study), aid characteristics and impact on firms' international growth was identified, analysed and manually coded by the research team following the scheme in Table 2. We followed López‐Duarte and Vidal‐Suárez (2021) to classify ODA flows according to different criteria (e.g., multilateral/bilateral, conditioned aid, ODA formulas, recipients' needs, donors' interests and tied aid). Recipient countries were classified according to their level of income (four categories by the OECD) and type of government (three categories of democratic development by the Economist Intelligence Unit).…”
Section: Methodology: Identification Selection and Analysis Of Articlesmentioning
confidence: 99%
“…While the focus on the institutional logic of democratic governments thus reflects both the theoretical and the empirical mainstream, CSPs may also be affected by authoritarian logics. In particular, international cooperation for development aid is frequently organized in CSPs (Lopez‐Duarte & Vidal‐Suarez, 2021; Manning & Roessler, 2014; Vestergaard et al., 2021), and the goal of such partnerships is often the development of democratic institutions in the first place (Kolk & Lenfant, 2015). In this case, an additional source of institutional complexity is the multiplicity of the involved government logics, with spending countries being democratic and receiving countries being authoritarian or hybrid, or being in conditions of fragile statehood.…”
Section: Advancing An Institutional Approach To Cross‐sector Partners...mentioning
confidence: 99%
“…was evident when the United Nations in 2015 established the 2030 agenda that included 17 sustainable development goals (SDGs; UN, 2015), breaking down this objective into four (Kumar et al, 2016;L opez-Duarte & Vidal-Suárez, 2021): End poverty in all its forms everywhere; End hunger, achieve food security and improved nutrition and promote sustainable agriculture; Promote sustained, inclusive and sustainable economic growth, full and productive employment and decent work for all; and Build resilient infrastructure, promote inclusive and sustainable industrialization, and foster innovation. The SDGs point to important problems for humanity that have not yet been solved (Arnold, 2018).…”
mentioning
confidence: 99%
“…The SDGs point to important problems for humanity that have not yet been solved (Arnold, 2018). The crisis caused by the Covid accentuates the importance of these goals (L opez-Duarte & Vidal-Suárez, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation